1994
DOI: 10.1080/01140671.1994.9513841
|View full text |Cite
|
Sign up to set email alerts
|

Maize production potential and climatic risk in the South Island of New Zealand

Abstract: Maize production is expanding in the South Island of New Zealand even though the climate is cool and variable, and marginal for reliable production of the crop. Its productivity in the region was assessed in field experiments conducted at Lincoln, Canterbury, during three contrasting seasons-two warmer and one cooler than average for the region. Three cultivars with different maturity characteristics were sown on several dates in each season. Even though the deviations from the longterm mean seasonal temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
3
2
0
Order By: Relevance
“…The lack of correlation between biomass yield and biomass N percentage in the present study has been observed in earlier studies (Hunter 1986) and supports the contention that it may be feasible to develop hybrids with both high yield and high crude protein, although there is little genetic variation in this trait. The high percentage grain in the early maturing hybrids (Table 4) agrees with results obtained at Lincoln, New Zealand (Wilson et al 1994), and may be the result of increased time available for partitioning dry matter into the grain (Deloughery & Crookston 1979) in early hybrids and decreased radiation use efficiency resulting from lower average temperatures during grain-fill for later hybrids (Wilson et al 1995). Plant population had little effect on percentage grain, indicating that environmental conditions (moisture and fertility) were not seriously limiting during most of the growing season (Duncan 1975).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The lack of correlation between biomass yield and biomass N percentage in the present study has been observed in earlier studies (Hunter 1986) and supports the contention that it may be feasible to develop hybrids with both high yield and high crude protein, although there is little genetic variation in this trait. The high percentage grain in the early maturing hybrids (Table 4) agrees with results obtained at Lincoln, New Zealand (Wilson et al 1994), and may be the result of increased time available for partitioning dry matter into the grain (Deloughery & Crookston 1979) in early hybrids and decreased radiation use efficiency resulting from lower average temperatures during grain-fill for later hybrids (Wilson et al 1995). Plant population had little effect on percentage grain, indicating that environmental conditions (moisture and fertility) were not seriously limiting during most of the growing season (Duncan 1975).…”
Section: Discussionsupporting
confidence: 87%
“…The biomass yields obtained ranged between 15 800 and 20 700 kg DM/ha, similar to the yields reported in Canterbury (Wilson et al 1994) in years with average or higher than average temperatures. Differences among hybrids generally reflected their maturity ranking (Graybill et al 1991).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…A renewed interest in supplementary feeds such as whole crop silage (de Ruiter et al 2002;Milne 2007;Platfoot & Stevens 2002) maize silage (Dalley et al 2005;Densley et al 2005b) and brassicas (Hogg et al 2002) has been driven by the demand for higher per cow performance. Maize for silage has been considered in southern latitudes (Wilson et al 1994) with the main option being short maturing hybrids to reduce the risk of crop failure. Summer fed turnips (Eerens & Lane 2004) and grazing-type brassicas such as leafy turnips (2009) Proceedings of the New Zealand Grassland Association 71: [107][108][109][110][111][112][113][114][115][116] treatments in the second sequence (Sequence 2) in the autumn and winter of Year 1 (Table 1).…”
Section: Introductionmentioning
confidence: 99%